The New Birth in Christ: A Neoevangelical Approach - Łukasz Krauze (Annales Missiologici Posnanienses)
The call to conversion has its roots in the Gospel. On this basis, evangelical preachers call on their listeners to turn from sin, repent of it, and believe in Jesus Christ. Preaching without this message is meaningless. It deprives the listener of the opportunity to awaken to Christian life and grow in faith. Conversionism is the belief that every person’s life needs to change, to be given a new direction. One of the essential elements of conversionism is the new birth in Christ.